THE METHOD OF TREATMENT OF PRIMARY ULCERATIVE GINGIVITIS - N.M. Ilenko; I.Yu. Popovych; A.V. Marchenko; I.Yu. Lytovchenko; E.V. Nikolishyna (Український стоматологічний альманах)
Despite the relatively low prevalence, necrotizing ulcerative gingivitis is the most severe among gingivitis, associated with microflora of dental biofilm and very rapid tissue destruction. The study involved 12 patients, aged 22-27 years, with acute necrotizing ulcerative gingivitis (ANUG). The new treatment approach, that was developed and tested by the authors, was used in the therapy of all ANUG patients. The treatment was considered effective in achieving positive results in the clinical picture of the disease and laboratory tests. On day 3 of gingivitis treatment, all patients subjectively noted a significant improvement in general condition, alleviation of pain. On day 7 following the treatment, subjectively, all patients had no complaints, and, objectively, the absence of edema and redness in the affected areas of the gums was noted in 9 (75%) patients; in 3 (25%) patients, a slight redness of the gums of the marginal area was detected, as well as the presence of non-mineralized dental plaque. The proposed method of treatment with the use of Tantum Verde spray as part of the complex therapy is effective, easy to use and can be recommended for use in dentistry as the anti-inflammatory therapy of primary ulcerative gingivitis. Perspectives of further research will encompass the follow up search for the effective methods of comprehensive treatment of patients with uncreative gingivitis.